Secondary sex estimation using morphological traits from the cranium and mandible: application to two Merovingian populations from Belgium - Bérénice Chevalier; Frédéric Santos; Caroline Polet; Sébastien Villotte (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
It is generally accepted that the coxal bone is the most reliable bone for estimating the sex of adult subjects. When the coxal bone is not usable, researchers generally turn to methods based on the skull (cranium and mandible). However, these methods are less reliable, because they are largely based on an estimate of the robusticity, which can be influenced by characteristics independent of the sex of the subject. In the context of primary sex estimation, skull-based methods should therefore be avoided. However, by using morphological traits of the cranium and the mandible as part of a secondary sex estimation, we were able to estimate the sex of a relatively large number of individuals with a minimum reliability of 95%. Our study thus illustrates the value of using morphological characteristics of the skull for a secondary sex estimation conducted with a reliable statistical method.